Programa Casa Nova, Vida Nova e política de desenvolvimento territorial : habitação de interesse social no alto sertão sergipano - Andrade, Vanilza da Costa (2013)
This dissertation aims to analyze the policy of social housing and its implications in the production in high hinterland area - Sergipe, through two operation modes - concentrated and pulverized. Reaching that goal, we opted for the method of historical materialism and dialectical understanding the politics of social housing in a historical movement (present / past), analyzing the contradictions that reveal the essence of social policy. The housing analysis in Brazil was grounded in its social, economic and historical, highlighting the role of housing policies for the service of the dominant class interests. With the changes in Brazil, after the redemocratization process and ended the developmental model, it introduces a new model in which domination is through consensus, disguised in a democratic and participatory management. In order to reveal the contradictions of territorial development policy, the study was conducted by Program New Home, New Life that is inserted into the New Territorial Development Policy of Sergipe, since 2007. In this program, the concentrated form (housing) is embedded in spatial development policy which reaffirms the need of a territorial identity creation. Because of this policy, what we see is the responsibility of people solving their problems, as well as the acquisition of their house is done via a selection, which in most cases, local political power is that defines the people who will be benefited , feeding the old / new patronage relationships. On the other hand, in the pulverized mode is highlighted the Smallholders Movement that paradoxically triggers a program established by the State to strengthen its fight to maintain the man in the agricultural field, able to live and dwell in it. In Sergipe, the smallholders Movement acts on the territory of High hinterland and one of their fights is the Peasant House which is characterized by the construction of houses in lands of those who are part of the movement, without political interference. Thus, in the reality studied, the Program New Home, New life goes deep in the vulnerability of social subjects, because the territorial development policy has reproduced patronage practices, in addition to feeding the financial relationships that are necessary for the house acquisition.